Carbon–Fluorine Reductive Elimination from Nickel(III) Complexes. (11th May 2017) - Lee, Heejun; Börgel, Jonas; Ritter, Tobias
Abstract: We report a C−F reductive elimination from a characterized first‐row aryl metal fluoride complex. Reductive elimination from the presented nickel(III) complexes is faster than C−F bond formation from any other characterized aryl metal fluoride complex.